Correlates of Peripheral Blood Mitochondrial DNA Content in a General Population - Knez, Judita; Winckelmans, Ellen; Plusquin, Michelle; Thijs, Lutgarde; Cauwenberghs, Nicholas; Gu, Yumei; Staessen, Jan A.; Nawrot, Tim S.; Kuznetsova, Tatiana (American journal of epidemiology, 2016)
Accumulation of mitochondrial DNA (mtDNA) mutations leads to alterations of mitochondrial biogenesis and function that might produce a decrease in mtDNA content within cells. This implies that mtDNA content might be a potential biomarker associated with oxidative stress and inflammation. However, data on correlates of mtDNA content in a general population are sparse. Our goal in the present study was to describe in a randomly recruited population sample the distribution and determinants of peripheral blood mtDNA content. From 2009 to 2013, we examined 689 persons (50.4% women; mean age = 54.4 years) randomly selected from a Flemish population (Flemish Study on Environment, Genes, and Health Outcomes). Relative mtDNA copy number as compared with nuclear DNA was measured by quantitative real-time polymerase chain reaction in peripheral blood. There was a curvilinear relationship between relative mtDNA copy number and age. mtDNA content slightly increased until the fifth decade of life and declined in older subjects (Page (2) = 0.0002). mtDNA content was significantly higher in women (P = 0.007) and increased with platelet count (P < 0.0001), whereas it was inversely associated with white blood cell count (P < 0.0001). We also observed lower mtDNA content in women using estroprogestogens (P = 0.044). This study demonstrated in a general population that peripheral blood mtDNA content is significantly associated with sex and age. Blood mtDNA content is also influenced by platelet and white blood cell counts and estroprogestogen intake. Further studies are required to clarify the impact of chronic inflammation and hormone therapy on mitochondrial function.